Analysis of the latitudinal variability of tropospheric ozone in the Arctic using the large number of aircraft and ozonesonde observations in early summer 2008 - Ancellet, Gérard; Daskalakis, Nikolaos; Raut, Jean-Christophe; Tarasick, David; Hair, Jonathan; Quennehen, Boris; Ravetta, François; Schlager, Hans; Weinheimer, Andrew J.; Thompson, Anne M.; Johnson, Bryan; Thomas, Jennie L.; et al. (Atmospheric Chemistry and Physics, 2016)
International audience During the 2008 International Polar Year, the POLARCAT (Polar Study using Aircraft, Remote Sensing, Surface Measurements, and Models of Climate Chemistry, Aerosols, and Transport) campaign, conducted in summer over Greenland and Canada, produced a large number of measurements from three aircraft and seven ozonesonde stations. Here we present an observation-integrated analysis based on three different types of O 3 measurements: airborne lidar, airborne UV absorption or chemiluminescence measurement, and intensified electrochemical concentration cell (ECC) ozonesonde profiles. Discussion of the latitudinal and vertical variability of tropospheric ozone north of 55° N during this period is performed with the aid of a regional model (WFR-Chem). The model is able to reproduce the O 3 latitudinal and vertical variability but with a negative O 3 bias of 6–15 ppbv in the free troposphere above 4 km, especially over Canada. For Canada, large average CO concentrations in the free troposphere above 4 km ( > 130 ppbv) and the weak correlation (< 30 %) of O 3 and PV suggest that stratosphere–troposphere exchange (STE) is not the major contributor to average tropospheric ozone at latitudes less than 70° N, due to the fact that local biomass burning (BB) emissions were significant during the 2008 summer period. Conversely, significant STE is found over Greenland according to the better O 3 vs. PV correlation ( > 40 %) and the higher values of the 75th PV percentile. It is related to the persistence of cyclonic activity during the summer over Baffin Bay. Using differences between average concentration above Northern and Southern Canada, a weak negative latitudinal summer ozone gradient of −6 to −8 ppbv is found in the mid-troposphere between 4 and 8 km. This is attributed to an efficient O 3 photochemical production from BB emissions at latitudes less than 65° N, while the STE contribution is more homogeneous in the latitude range 55–70° N. A positive ozone latitudinal gradient of 12 ppbv is ...